Electrocatalysis under a magnetic lens: A combined electrochemistry and electron paramagnetic resonance review. (1st March 2022) - den Hartog, Stephan; Neukermans, Sander; Samanipour, Mohammad; Ching, H.Y. Vincent; Breugelmans, Tom; Hubin, Annick; Ustarroz, Jon
Highlights: Contemporary electrocatalysis and electron paramagnetic resonance review. In situ electrochemical cell design for EPR. Mechanistic and quantification studies. Advanced (pulse) EPR for electrochemistry. Abstract: Electron paramagnetic resonance (EPR) spectroscopy is not considered a standard technique within the electrochemist's toolkit. It was used more frequently in electrocatalysis research from the 1960′s until the 1990′s to identify paramagnetic reaction intermediates and elucidate reaction mechanisms, but is less used nowadays. Since the 1990′s however, technological progress has made advanced EPR methods more readily available, which has allowed for more sensitive measurements and better identification of intermediate species. Furthermore, developments in additive manufacturing have made it easier and cheaper to construct specialized electrochemical cells for EPR research. This review aims to provide a critical overview of contemporary research combining electrocatalysis and EPR, and at the same time spark renewed interest in the combination of these two techniques. It is divided into three sections. Firstly, it covers the challenges involved with in situ cell design and gives an overview of recent cell designs. Next, a number of contemporary mechanistic and quantitative studies are reviewed to explore the possibilities of EPR spectroscopy. Finally, it covers advanced pulse EPR techniques and their (so far) limited use in electrocatalytic research. Graphical abstract: Image, graphical abstract